2002
DOI: 10.1590/s1519-69842002000400016
|View full text |Cite
|
Sign up to set email alerts
|

Cladocera Chydoridae of high altitude water bodies (Serra da Mantiqueira), in Brazil

Abstract: The diversity of species of Cladocera, Chydoridae in the water bodies belonging to the water management unity of Serra da Mantiqueira, was studied inside the BIOTA/FAPESP Program. A total of 21 water bodies were analyzed and the sampling was carried out between 9 th and 11 th September, 1999. Horizontal and vertical net hauls were taken at littoral and limnetic region in each lake. Most water bodies in Serra da Mantiqueira unity are small, shallow, and densely colonized by macrophytes. Most species of Cladocer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 16 publications
(14 reference statements)
1
17
0
7
Order By: Relevance
“…The number of Cladocera species found in the wetlands studied is very similar to other studies conducted in Brazil for the littoral zone of inland water ecosystems or environments colonized by macrophytes (Santos-Wisniewski et al 2002, Lima et al 2003, Sousa et al 2009, Elmoor-Loureiro 2007, Maia-Barbosa et al 2008, Soares & ElmoorLoureiro 2011. In all these studies, a greater contribution of the Chydoridae family was verified in the number of species, which was also observed in the wetlands sampled here, and this seems to be a pattern of faunal composition that is very common in studies of the littoral zone of water systems.…”
Section: Discussionsupporting
confidence: 87%
“…The number of Cladocera species found in the wetlands studied is very similar to other studies conducted in Brazil for the littoral zone of inland water ecosystems or environments colonized by macrophytes (Santos-Wisniewski et al 2002, Lima et al 2003, Sousa et al 2009, Elmoor-Loureiro 2007, Maia-Barbosa et al 2008, Soares & ElmoorLoureiro 2011. In all these studies, a greater contribution of the Chydoridae family was verified in the number of species, which was also observed in the wetlands sampled here, and this seems to be a pattern of faunal composition that is very common in studies of the littoral zone of water systems.…”
Section: Discussionsupporting
confidence: 87%
“…Like the Nyanga reservoirs, these waterbodies were densely colonized by macrophytes and were dominated by the Chydoridae, which typically inhabit the littoral zone living in association with macrophyte vegetation. The results was evidence of the importance of the littoral zone as favourable habitats Chydoridae species and thereby contributing to the overall diversity of cladocerans (Santos-Wisniewski et al 2002).…”
Section: Discussionmentioning
confidence: 84%
“…A study in Kenya on eight small montane reservoirs (Mwuara et al 2002) revealed a zooplankton community that was composed mainly of crustaceans, rotifers and protozoa in. The zooplankton community of 21 montane water bodies were also studied in Brazil (Santos-Wisniewski et al 2002). Like the Nyanga reservoirs, these waterbodies were densely colonized by macrophytes and were dominated by the Chydoridae, which typically inhabit the littoral zone living in association with macrophyte vegetation.…”
Section: Discussionmentioning
confidence: 99%
“…Foram identificadas 11 espécies de Cladocera no açude Fazenda Lagoa, sendo que 6 pertencem a família Chydoridae. As espécies da família Chydoridae são típicas de região litorânea e vivem associadas aos bancos de macrófitas, utilizando para a alimentação apêndices especializados na raspagem de substratos (SANTOS-WISNIEWSKI et al, 2002). Também foi observada a ocorrência da espécie Scapholeberis armata, um representante da família Daphnidae que vive ligado à tensão superficial da água (ROCHA;GÜNTZEL, 2000).…”
Section: Discussõesunclassified